Prevalence and Profile of Patients with Otitis Externa at the Universitas Sumatera Utara Hospital in Medan in 2020-2021 - Qatrunnada Medina Salim; Adlin Adnan; Indri Adriztina; Iman Dwi Winanto (Universitas Muhammadiyah Sumatera Utara, 2023)
Otitis externa is an acute or chronic inflammation of the ear canal which also involves the tympanic membrane and pinna. This disease has a prevalence rate of about 10% of all ENT diseases. Aim. This research aims to determine the prevalence and profile of the disease based on demographic characteristics (age, sex, and occupation), chief complaint, type, location, and comorbidities in patients with otitis externa. Methods. This research is a hospital-based retrospective study of patients diagnosed with otitis externa in Universitas Sumatera Utara Hospital Medan for the period January 2020 to December 2021. Data were obtained from medical records then processed using the SPSS program and analyzed using descriptive statistics. Results. The total number of patients in Universitas Sumatera Utara Hospital for the 2020-2021 period who met the study inclusion and exclusion criteria was 291 patients. Found 47.4% male and 52.6% female with a ratio of 1:1.1. The peak age group at 26-45 years was 36.8%. In employment status, 23.0% are self-employed and patients who do not work 22.7% are the majority while 0.3% POLRI of and laborers are a minority. The majority 72.5% come with a chief complaint of pain or tenderness in the ear followed by 10% of the ear that felt full. The most common type of otitis externa was acute diffuse as much as 91.8% with the location of the right ear that was most often complained of as much as 44.7%. Otitis externa disease is commonly found in patients who do not have other comorbidities as much as 87.3%. Conclusion. Otitis externa is a common ear disease that affects all age groups and genders. Most of the patients come with complaints of pain in the right ear and were diagnosed with acute diffuse otitis externa.